Antioxidant Properties and Diet-Related α-Glucosidase and Lipase Inhibitory Activities of Yogurt Supplemented with Safflower (Carthamus tinctorius L.) Petal Extract - Hong, Heeok; Lim, Jeong Min; Kothari, Damini; Kwon, So Hee; Kwon, Hyuk Cheol; Han, Sung-Gu; Kim, Soo-Ki (Food science of animal resources, 2021)
Recently, yogurt has been extensively studied to further enhance its functions using edible plant extracts. This study was conducted to investigate whether safflower petal (SP) as a natural food additive can be used to develop functional yogurt with improved health benefits. SPs were extracted with ethanol (SPE) and hot water (SPW), and then safflower yogurt was prepared by adding 0%-1.0% of those extracts to plain yogurt. With an increase in the fermentation duration, the pH of SPE and SPW yogurt samples was decreased, whereas titratable acidity and microbial counts were increased. The concentration of total polyphenols and total flavonoids, the activity of antioxidants, and the inhibitory effect on reactive oxygen species (ROS) were higher in SPW yogurt than SPE yogurt. Furthermore, α-glucosidase and lipase activity inhibitory effects of SPW yogurt were higher than those of SPE yogurt. In particular, free radical-scavenging activities, ROS inhibitory effect, and α-glucosidase activity inhibitory effects were significantly increased in SPW yogurt in a dose-dependent manner. Overall, these results suggest that SP extract possesses antioxidant activities and that it can downregulate α-glucosidase and lipase activities. The SP extract may have potential benefits as a natural food additive for the development of functional yogurt.